Prediction of psychological well-being based on attitude toward religion and death anxiety in the elderly men of Kermanshah's part-time elderly care center - Payam Varaee; Khodamorad Momeni; Asie Moradi (Shahid Beheshti University of Medical Sciences, 2018)
For downloading the full-text of this article please click here. Background and Objective: Considering the vital importance of the elderly's well-being and the rapid growth of their populations, studying the role of various variables in the well-being of the elderly is necessary; therefore, the present study was conducted with the aim of investigating the relationship between psychological well-being and religiosity and death anxiety in the elderly. Method: This research adopted a descriptive, correlational design. The statistical population of this study consisted of all elderly men in Kermanshah's part-time elderly care centers comprising 700 people in total. Out of this population, 200 individuals were selected by simple random sampling. The research instruments were Psychological Well-Being Questionnaire (Ryff, 1989), Muslim Attitudes toward Religion (Wilde and Joseph, 1997), and Death Anxiety Inventory (Templer, 1970). Entry criteria included: 1) a score of 22 at the cognitive state test, 2) a minimum age of 60 years, 3) a minimum of junior high school education, 4) enough monthly earnings. People who did not have these conditions were excluded. Pearson correlation coefficient and stepwise multiple regression were used for data analysis. All ethical issues were observed in the study and the researchers declared no conflict of interests. Results: The findings showed that there was a significant, positive relationship between psychological well-being and religiosity (r= 0.39, P<0.001) and a measurable, negative association between psychological well-being and death anxiety (r=-0.19, P<0.001). The results of stepwise regression analysis also showed that Islamic attitude, death anxiety, and Islamic rituals can significantly predict 22% of psychological well-being in elderly people (P<0.001). Conclusion: Overall, psychological well-being can be increased in the elderly through increasing attention to the role of religiosity in life and the application of strategies that reduce the anxiety of death. For downloading the full-text of this article please click here.